Isolation and Extraction of Medicinally Useful Dye from the Roots of Arnebia nobilis Rech. f., Using Different Solvents - Indrayan, A.K.; Yadav, Vimla (Asian Journal of Chemistry, 2010)
Root of Arnebia nobilis, a native of Afghanistan but available freely in India, is the source of medicinally useful dyes. It serves as colouring matter as well as for the treatment of certain ailments. Using the various solvents for extraction, viz., water, methanol (reflux and cold), aqueous caustic soda, caustic soda extract neutralized with HCl, and n-hexane, the dark brown solid (brownish orange solution), red-black solid (crimson red and maroon solutions), black semi-solid (deep blue solution), chocolate coloured solid (deep blue solution), and dark red viscous substance (dark red solution) respectively are obtained, expected to have varied medicinal value.